Evaluation of Oral Medication Delivery Devices Provided by Community Pharmacies. (May 2013) - Honey, Brooke L.; Condren, Michelle; Phillips, Christina; Votruba, Allyson
Oral liquids remain common medication dosage forms used for patients who have difficulty swallowing. However, liquids require a delivery device and thus have been linked to medication administration errors. This study identified medication delivery devices available at pharmacies. Delivery devices were obtained from area pharmacies and analyzed for units of measurement, abbreviations, and largest/smallest measurable volume. A total of 58 devices were collected from 22 pharmacies. All devices were marked with mL, and 79% were additionally marked in teaspoons. The 5-mL syringe was the only device dispensed at 14% of locations. Other devices included the dosing spoon, dropper, and cup. The largest measurable volume was 30 mL, whereas the smallest was 0.01 mL, with significant variability among devices. A more consistent approach in prescribing units of measurement is needed. Prescribing in milliliters is an optimal choice because of the accessibility of measuring devices containing this measurement.